Pengaruh Konsentrasi Naoh dan Laju Alir Gas pada Proses Pemurnian Biogas - Hermanto Hermanto; Arba Susanty (Balai Riset dan Standardisasi Industri Samarinda, 2016)
Biogas contain a number of other impurities such as hydrogen sulfide (H2S) and carbon dioxide (CO2). The presence of carbon dioxide can decrease the burning calorie value while hydrogen sulfide is corrosive to many metals. Through modification of gas purification equipment (water scrubber), hydrogen sulfide gas (H2S) is captured by water to formed H2SO4, followed by the purification process with NaOH. The water residue will adsorb using silica gel. In this study, the factors to be studied are the variation of the concentration of NaOH and gas flow rate. The purpose of this study was to determine the influence of NaOH concentration and flow rate of gas in the gas content of CO2, H2S and pH value on biogas produced from domestic wastewater. Results of this studyshowed the ability of modification gas purification equipment to reduce the content of carbon dioxide and hydrogen sulfide of biogas. There are significantdifferences of pH, concentration of CO2 and H2S at the inlet and outlet of the reactor purification of biogas.The treatment bygas flow rate (3,75mL/min) and 3N of NaOH concentration significantly influence the change in pH, the concentration of CO2 and H2S. This treatment can reduce the CO2 content (71,9%), H2S content (100%) and pH (3,82).ABSTRAKBiogas mengandung sejumlah gas-gas pengotor lain seperti gas hidrogen sulfida (H2S) dan karbondioksida (CO2). Adanya gas CO2 dapat menurunkan nilai kalori pembakaran sedangkan H2S bersifat korosif bagi berbagai jenis logam.Modifikasi alat pemurnian gas (water scrubber) , gas H2Sakan ditangkap dengan air membentuk H2SO4, dilanjutkan proses pemurnian dengan NaOH sedangkan sisa air diadsorbsi menggunakan silica gel. Pada penelitian ini faktor perlakuan adalah variasi konsentrasi NaOH dan laju alir gas.Sehingga tujuan penelitian ini adalah mengetahui pengaruh konsentrasi NaOH dan laju alir gas pada reaktor pemurnian biogas terhadap kandungan gas CO2 , H2S dan nilai pH pada biogas.Hasil penelitian menunjukkanbahwa kemampuan modifikasi alat pemurnian gas dapat menurunkan kandungan gas CO2 dan H2S biogas. Perlakuan laju alir (3,75 mL/min) dan konsentrasi larutan NaOH (3N) berpengaruh secara signifikan terhadap perubahan pH air, konsentrasi CO2 dan H2S. Perlakuan ini dapat menurunkan kandungan CO2 sebesar 71,9%, kandungan H2S sebesar 100% dan nilai pH 3,82.Kata kunci : Biogas, pH, karbondioksida, hidrogensulfida, NaOH dan laju alir